2004
DOI: 10.1007/s00253-004-1599-1
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of the hinge region of nisinZ and properties of nisinZ mutants

Abstract: To study the role of the hinge region in nisin and to obtain mutants that exhibit altered or new biological activities and functional properties, we changed certain amino acids in the hinge region by performing site-directed mutagenesis with the nisinZ structural gene ( nisZ). The results showed that the nisinZ mutants had decreased antimicrobial activities against Micrococcus flavus NCIB8166 and Streptococcus thermophilus. Interestingly, compared with wild nisinZ, mutant N20K nisinZ and M21K nisinZ displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 30 publications
8
120
0
Order By: Relevance
“…Although the α peptides are usually cationic, they all possess at least one negatively charged residue and as a consequence of being N20H, N20R, M21H, M21R, K22H, K22R and N20K/M21K, generally had a slightly negative impact, 28,29 exceptions were apparent as the N20K and M21K peptides showed enhanced activity against Gram negative pathogenic bacteria such as Shigella, Salmonella and Pseudomonas. 28 However some variants in which a positive charge were removed, i.e., K22T and K22S, also brought about enhanced activity against targets such as Streptococcus agalactiae and Staphylococcus aureus. 29 In contrast to the varying consequences of manipulating positively charged residues within the nisin hinge, the introduction of negatively charged residues (N20E, N20D, M21E, K22E and K22D) consistently had negative consequences.…”
Section: Investigating the Importance Of Charged Residues In Lantibiomentioning
confidence: 99%
See 1 more Smart Citation
“…Although the α peptides are usually cationic, they all possess at least one negatively charged residue and as a consequence of being N20H, N20R, M21H, M21R, K22H, K22R and N20K/M21K, generally had a slightly negative impact, 28,29 exceptions were apparent as the N20K and M21K peptides showed enhanced activity against Gram negative pathogenic bacteria such as Shigella, Salmonella and Pseudomonas. 28 However some variants in which a positive charge were removed, i.e., K22T and K22S, also brought about enhanced activity against targets such as Streptococcus agalactiae and Staphylococcus aureus. 29 In contrast to the varying consequences of manipulating positively charged residues within the nisin hinge, the introduction of negatively charged residues (N20E, N20D, M21E, K22E and K22D) consistently had negative consequences.…”
Section: Investigating the Importance Of Charged Residues In Lantibiomentioning
confidence: 99%
“…29 In contrast to the varying consequences of manipulating positively charged residues within the nisin hinge, the introduction of negatively charged residues (N20E, N20D, M21E, K22E and K22D) consistently had negative consequences. 28 Finally, a number of charge variants have been created in which the N-terminal ring A of nisin A had been altered, i.e., KFI, KSI, TKI (letters represent the amino acids in ring A corresponding to positions 4-6 which are normally occupied by the uncharged residues IDhaL). The impact of the newly incorporated lysine residue was found to be location specific as both the KFI-and KSI-containing peptides exhibited enhanced activity whereas a TKI mutant retained no antimicrobial activity.…”
Section: Investigating the Importance Of Charged Residues In Lantibiomentioning
confidence: 99%
“…However, not all of these genes have been detected in the gene clusters, indicating that some of the regulatory and accessory genes may be located outside the gene cluster or that the gene functions can be provided by host-encoded proteins having similar activities (Heidrich et al, 1998). To study the function of the genes, several expression systems for production of lantibiotics have been constructed (Kuipers et al, 1992;Yuan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Saturation mutagenesis at another location in nisin, lysine 12, resulted in the finding that a K12A derivative displays increased specific activity against food pathogens such as B. cereus, S. aureus and S. agalactieae but not against L. monocytogenes [33]. Another region of the nisin peptide, the three amino acid 'hinge' region, is particularly amenable to change and bioengineering of this region has had beneficial consequences [34]. Indeed, Rouse et al [35] created a bank of hinge mutants and found that nisin peptides containing hinges consisting of SVA or NAK (rather than the original NMK) displayed an enhanced ability to diffuse through complex polymers, a trait which enabled the variants to outcompete nisin A controlling L. monocyto genes in commercially produced chocolate milk containing the stabiliser carrageenan.…”
Section: Bacteriocin Engineeringmentioning
confidence: 99%